Critical Realism and the Sun Paradigm : The Nature and Logic of Critical Realism as a New Socio-Scientific Paradigm - Shakespeare, Rodney (Journal of Critical Realism in Socio-Economics (JOCRISE), 2022)
A ‘paradigm’ is a mindset based on interconnected assumptions and underpinnings which appear to be self-evident truths. It is thus an intellectual structure founded on connected components while being, at the same time, an understanding of reality. Paradigms decide what does, or does not, happen. A shift to accurate paradigm opens the way for much positive and beneficial change. A new paradigm cannot be understood by using the analysis and understandings of the old paradigm. It can only be understood in terms of its own new analysis and understandings